2001
DOI: 10.3354/meps223143
|View full text |Cite
|
Sign up to set email alerts
|

Interactive roles of mesograzers and current flow in survival of kelps

Abstract: ABSTRACT:The relationship between hydrodynamic energy and biological processes is examined for a kelp-dominated marine community in the San Juan Archipelago. Populations of a common and widely distributed kelp, Nereocystis luetkeana, were established and rates and causes of mortality followed at 7 sites differing greatly in tidally driven current velocities and wave exposure (measured by permanently deployed instrument packages). Mortality of N. luetkeana was not related to storm energy, but exhibited a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 28 publications
2
95
2
Order By: Relevance
“…Many seaweed species (mainly Phaeophyceae) possess pneumatocysts that keep submerged algal fronds in an upright position and allow them to float after detachment. When detached from their substratum by wave action (Seymour et al, 1989), herbivorous feeding activity (Duggins et al, 2001), or as a natural event in the alga's life cycle (Thomsen et al, 2004) buoyant macroalgae rise up to the sea surface and carry with them a diverse epifaunal community from the benthic habitat.…”
Section: Introductionmentioning
confidence: 99%
“…Many seaweed species (mainly Phaeophyceae) possess pneumatocysts that keep submerged algal fronds in an upright position and allow them to float after detachment. When detached from their substratum by wave action (Seymour et al, 1989), herbivorous feeding activity (Duggins et al, 2001), or as a natural event in the alga's life cycle (Thomsen et al, 2004) buoyant macroalgae rise up to the sea surface and carry with them a diverse epifaunal community from the benthic habitat.…”
Section: Introductionmentioning
confidence: 99%
“…A H/W ratio between 4.4 and 6.4 is ideal for sites with moderate current velocity (Gardner 1980). Although not measured in this study, Duggins et al (2001) found average current speed at Cantilever Point (-8 m MLLW) to be less than 10 cm s -1 and velocities at Saddlebag Island were suspected to be similar (authors' pers. obs.).…”
Section: Methodsmentioning
confidence: 99%
“…N. luetkeana forms a natural persistent bed in the north cove of Saddlebag Island (48°32.93' N, 122°33.41' W) in Padilla Bay. At a second site, N. luetkeana previously was established experimentally (Duggins et al 2001) at Cantilever Point on San Juan Island (48°32.84' N, 123°0.23' W) in the San Juan Archipelago. Both sites are characterized by serpentine bedrock that is covered in places by shale and silt.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations